Thrombotic Events in MIS-C Patients: A Single Case Report and Literature Review - Maniscalco, Valerio; Niccolai, Rachele; Marrani, Edoardo; Maccora, Ilaria; Bertini, Federico; Pagnini, Ilaria; Simonini, Gabriele; Lasagni, Donatella; Trapani, Sandra; Mastrolia, Maria Vincenza (Children (Basel), 2023)
Multisystem Inflammatory Syndrome in Children (MIS-C) is a systemic hyperinflammatory disorder that is associated with a hypercoagulable state and a higher risk of thrombotic events (TEs). We report the case of a 9-year-old MIS-C patient with a severe course who developed a massive pulmonary embolism that was successfully treated with heparin. A literature review of previous TEs in MIS-C patients was conducted (60 MIS-C cases from 37 studies). At least one risk factor for thrombosis was observed in 91.7% of patients. The most frequently observed risk factors were pediatric intensive care unit hospitalization (61.7%), central venous catheter (36.7%), age >12 years (36.7%), left ventricular ejection fraction <35% (28.3%), D-dimer >5 times the upper limit of normal values (71.9%), mechanical ventilation (23.3%), obesity (23.3%), and extracorporeal membrane oxygenation (15%). TEs may concurrently affect multiple vessels, including both arterial and venous. Arterial thrombosis was more frequent, mainly affecting the cerebral and pulmonary vascular systems. Despite antithrombotic prophylaxis, 40% of MIS-C patients developed TEs. Over one-third of patients presented persistent focal neurological signs, and ten patients died, half of whom died because of TEs. TEs are severe and life-threatening complications of MIS-C. In case with thrombosis risk factors, appropriate thromboprophylaxis should be promptly administered. Despite proper prophylactic therapy, TEs may occur, leading in some cases to permanent disability or death.